Dual enzyme co-immobilization on reversibly soluble polymers for the one-pot conversion of ferulic acid from wheat bran. (6th April 2022) - Wang, Kaipeng; Jin, Wenbin; Ding, Yiling; Lyu, Yongmei; Liu, Jinbin; Yu, Xiaohong
Abstract : Feruloyl esterase and xylanase were covalently co-immobilized onto a reversible soluble carrier Eudragit L-100. Abstract : The difficulty of using immobilized enzyme to decompose wheat bran to produce ferulic acid lies in the recovery of enzyme from solid-rich wheat bran hydrolysates. In this study, two enzymes (feruloyl esterase and xylanase) were successfully immobilized on the reversible soluble vector Eudragit L-100. The co-immobilized enzymes were used to decompose wheat bran to produce ferulic acid through the determination of enzymatic properties and catalytic conditions. The yield of ferulic acid reached 35% of the total ferulic acid content in wheat bran under these conditions. The reversible and soluble nature of the carrier made it simpler to recover co-immobilized enzymes from solid matrices. The co-immobilized enzymes could be reused for 5 cycles with more than 60% of the activity left, which verified the feasibility of using reversible soluble carrier to immobilize ferulic esterase and xylanase.